Prediction of best cloud service provider using the QoS ranking framework - S. Syed Fiaz, A; S. Guruprakash, K; S. Syed Navaz, A (International Journal of Engineering and Technology, 2017)
The ability to utilize the computing resources based on the need has taken the Cloud computing to a greater height and it has increased the potential to extend the flexibility and efficiency of any resource. Considering the advantages, there are various Cloud Services Providers (CSP) that can offer services based on the user request and finding optimal services among those Cloud Services can be a great dispute. The proposed work relies on a QoS Ranking prediction that chooses the appropriate services offered by the various different CSPs. Based on those predicted analysis, the best CSP will be marked with a Ranking framework, according to which the Services will be directed to the users.